Short-Term Effects of Land Leveling on Irrigation-Related Some Soil Properties in a Clay Loam Soil - Tekin Öztekin (The Scientific World Journal)
There are few studies conducted on the short-term effects of land leveling on soil water holding capacity. The objectives of this study were to analyze the short-term effects of land leveling on the magnitudes, variances, spatial variability, and distributions of surface (0–20 cm) and subsurface (20–40 cm) soil properties of bulk density, field capacity, permanent wilting point, water holding capacity and particle size fractions. The study was conducted in a 1.2 ha field with clay loam soil located on the low terraces of Yesilirmak River, Tokat, Turkey. According to the paired t-test results, water holding capacity, and bulk density significantly increased, while permanent wilting point (P ≤ 0.001) and field capacity (P ≤ 0.05) significantly decreased for surface soil due to land leveling. The reasons for the increases in WHC values in both cut and fill areas (29%, and 12%, resp.) of surface soil are look like the much more decreases in PWP values than those of FC values and the increases in BD values. The moderate positive linear relationship between the surface soil clay contents and cut depths through cut areas (r = 0.64) was also determined in this study.